Pickering emulsions stabilized with chitosan/collagen peptides nanoparticles as green topical delivery vehicles for cannabidiol (CBD) - Sharkawy, Asma (2018)
Pickering emulsions (PEs) are attracting increasing attention in the areas of food, cosmetic and pharmaceutical applications owing to their surfactant-free and eco-friendly nature. Herein, PEs stabilized by chitosan/collagen peptides (CH/CP) nanoparticles were assessed as green surfactant-free vehicles for the topical delivery of cannabidiol (CBD), a highly lipophilic unstable drug that is finding an increasing appeal in the cosmetic market. The influence of the oil phase volume fraction (φ) and the oil type on the emulsion properties, stability, rheological properties, as well as on the ex-vivo skin absorption of CBD was evaluated. The PE prepared with olive oil (φ = 0.6) exhibited elastic gel-like properties and demonstrated long-term stability after 5 months of storage, with a CBD content of 99.45% of the initially added amount. The skin absorption studies showed that CBD was retained in high amounts in the stratum corneum, while the CBD skin permeation was extremely low, indicating that the produced formulations are suitable as topical delivery vehicles. ATR-FTIR examination of the treated skin samples confirmed that the produced PEs were able to overcome the stratum corneum barrier. These findings suggest that the PEs stabilized with CH/CP nanoparticles provide an effective surfactant-free alternative for the topical delivery of CBD.